1999
DOI: 10.1016/s1360-1385(98)01364-8
|View full text |Cite
|
Sign up to set email alerts
|

Salicylic acid-independent plant defence pathways

Abstract: Salicylic acid is an important signalling molecule involved in both locally and systemically induced disease resistance responses. Recent advances in our understanding of plant defence signalling have revealed that plants employ a network of signal transduction pathways, some of which are independent of salicylic acid. Evidence is emerging that jasmonic acid and ethylene play key roles in these salicylic acid-independent pathways. Cross-talk between the salicylic acid-dependent and the salicylic acid-independe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
307
0
23

Year Published

2000
2000
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 571 publications
(343 citation statements)
references
References 56 publications
6
307
0
23
Order By: Relevance
“…The accumulation of SA in response to elicitors and pathogen challenge was earlier shown in pine (Davis et al 2002). SA is furthermore known to induce specific sets of PR genes (Pieterse and van Loon 1999) prior to the establishment of systemic acquired resistance (Grant and Lamb 2006). In contrast to the results with Sp-AMP, expression of Pm-AMP1, a homolog in western white pine (Pinus monitcola) that is involved in defence against the blister rust fungus Cronartium ribicola, is induced in healthy foliage 4 days after MeJA treatment (Ekramoddoullah et al 2006).…”
Section: Discussionmentioning
confidence: 76%
“…The accumulation of SA in response to elicitors and pathogen challenge was earlier shown in pine (Davis et al 2002). SA is furthermore known to induce specific sets of PR genes (Pieterse and van Loon 1999) prior to the establishment of systemic acquired resistance (Grant and Lamb 2006). In contrast to the results with Sp-AMP, expression of Pm-AMP1, a homolog in western white pine (Pinus monitcola) that is involved in defence against the blister rust fungus Cronartium ribicola, is induced in healthy foliage 4 days after MeJA treatment (Ekramoddoullah et al 2006).…”
Section: Discussionmentioning
confidence: 76%
“…Recent advances in research on plant defense signalling pathways have shown that plants are capable of di erentially activating distinct defense pathways depending on the type of invader encountered [36]. Upon pathogen infection, the production of JA and ethylene is stimulated, leading to the activation of speci®c defense-related genes [4,57].…”
Section: Discussionmentioning
confidence: 99%
“…These include systemic acquired resistance (SAR), which is triggered by necrotizing pathogens [1]; induced systemic resistance (ISR), which is activated upon colonization of roots by selected strains of non-pathogenic rhizobacteria [2]; and woundinduced defense, which is typically elicited upon tissue damage such as that caused by feeding insects ( [3]; Figure 1). Induced defense responses are regulated by a network of interconnecting signal transduction pathways in which the hormonal signals salicylic acid (SA), jasmonic acid (JA), and ethylene (ET) play a major role [4][5][6], and other hormones such as brassinosteroids and abscisic acid can also be involved [7][8][9].…”
Section: Introductionmentioning
confidence: 99%